2021
DOI: 10.1186/s12864-021-07979-3
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the gut microbiome in a porcine model of thoracic spinal cord injury

Abstract: Background The gut microbiome is a diverse network of bacteria which inhabit our digestive tract and is crucial for efficient cellular metabolism, nutrient absorption, and immune system development. Spinal cord injury (SCI) disrupts autonomic function below the level of injury and can alter the composition of the gut microbiome. Studies in rodent models have shown that SCI-induced bacterial imbalances in the gut can exacerbate the spinal cord damage and impair recovery. In this study we, for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
0
9
0
1
Order By: Relevance
“…(122). In a Yucatan minipig model with a contusioncompression SCI at T2 or T10, Doelman et al presented a dynamic view of the microbiome changes following SCI and identified acute stage, 0-14 post-SCI, as a special time-frame that many of the bacterial fluctuations occur before returning to "baseline" levels (120). SCI promotes intestinal leakiness and bacterial translocation associated with activation of immune cells in GALTs, by increasing the population of B cells, CD8 + T cells, DCs, and macrophages and decreasing CD4 + T cell counts (25).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…(122). In a Yucatan minipig model with a contusioncompression SCI at T2 or T10, Doelman et al presented a dynamic view of the microbiome changes following SCI and identified acute stage, 0-14 post-SCI, as a special time-frame that many of the bacterial fluctuations occur before returning to "baseline" levels (120). SCI promotes intestinal leakiness and bacterial translocation associated with activation of immune cells in GALTs, by increasing the population of B cells, CD8 + T cells, DCs, and macrophages and decreasing CD4 + T cell counts (25).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Firmicutes, Bacteroidetes, and Actinobacteria can digest carbohydrates, such as complex oligoglycans present in mucin [ 25 ]. The degradation of these carbohydrates produces short-chain fatty acids, which are reabsorbed by the host for energy [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was observed when gut microbiota was studied in SCI patients. SCI has been shown to affect the composition of the gut microbiota in experimental animals (111), and many bacteria can only return to normal levels after SCI fluctuations in the acute phase (112). It has been demonstrated that the gut microbiota of SCI patients differed from the healthy population's in terms of microbial community structure and quantity (113), Additionally, there may be a connection between serum markers, neurogenic bowel dysfunction, cardiovascular disease, and metabolic disorders and dysregulation of the gut microbiota (114,115).…”
Section: Microbiomicsmentioning
confidence: 99%